2009
DOI: 10.1021/pr800904z
|View full text |Cite
|
Sign up to set email alerts
|

Stable Isotope Dilution Multidimensional Liquid Chromatography-Tandem Mass Spectrometry for Pancreatic Cancer Serum Biomarker Discovery

Abstract: A novel approach to pancreatic cancer biomarker discovery has been developed, which employs a stable isotope labeled proteome (SILAP) standard coupled with extensive multidimensional separation coupled with tandem mass spectrometry (MS/MS). Secreted proteins from CAPAN-2 human pancreatic cancer derived cells were collected after conducting stable isotope labeling by amino acids in cell culture (SILAC). The resulting SILAP standard contained <0.5% of individual unlabeled proteins. Pooled sera from patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 43 publications
(84 reference statements)
3
75
1
Order By: Relevance
“…Thus far, many researchers have attempted to find novel biomarkers for pancreatic cancer using proteomic and transcriptomic approaches (Hibi et al 2009;Sitek et al 2009;Yu et al 2009), but their research findings have not demonstrated a practical use. Based on the findings of our current study, it was indicated that the pathogenesis of pancreatic cancer leads to variations in the serum levels of low molecular weight metabolites, and our study supports the potential of metabolomics as an early diagnostic tool for pancreatic cancer, although larger studies are needed to verify its practical utility.…”
Section: Resultsmentioning
confidence: 99%
“…Thus far, many researchers have attempted to find novel biomarkers for pancreatic cancer using proteomic and transcriptomic approaches (Hibi et al 2009;Sitek et al 2009;Yu et al 2009), but their research findings have not demonstrated a practical use. Based on the findings of our current study, it was indicated that the pathogenesis of pancreatic cancer leads to variations in the serum levels of low molecular weight metabolites, and our study supports the potential of metabolomics as an early diagnostic tool for pancreatic cancer, although larger studies are needed to verify its practical utility.…”
Section: Resultsmentioning
confidence: 99%
“…It remains unclear to date whether this complex peptidome may provide a robust correlation of biological events occurring in the entire organism. Therefore, this study aimed at identifying biomarkers that represent renal pathological status by taking the advantage of MS, which allows us to distinguish hundreds of small-to medium-sized peptides in microliters of serum [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…However, the progress of these studies has been hampered by the complex nature of serum/plasma samples and the large dynamic range between the concentrations of different proteins (14). As cancer biomarkers are likely to be present in low amounts in blood samples, the direct isolation of these markers from plasma and serum samples requires a labor-intensive process involving the depletion of abundant proteins and extensive protein fractionation prior to mass spectrometric analysis (15)(16)(17)(18). Alternatively, the secretome, or group of proteins secreted by cancer cells (19), can be analyzed to identify circulating molecules present at elevated levels in serum or plasma samples from cancer patients.…”
mentioning
confidence: 99%